PENGARUH DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DINAS KEBAKARAN DAN PENANGGULANGAN BENCANA KOTA BANDUNG - Ta'biul Kholiq Sarwana, Zulfi; Wahyuningtyas, Ratri (Jurnal Manajemen dan Profesional, 2023)
This research’s goal is to discover how work discipline affects employee performance at Dinas Kebakaran dan Penanggulangan Bencana Kota Bandung. This research employs quantitative methodology. The data were derived from the outcomes of distributing questionnaires to 143 employees who served as the research sample via the saturated sampling approach. The data was then evaluated utilizing descriptive analytic techniques and PLS-SEM analysis. The findings revealed that the level of work discipline and performance of employees at Dinas Kebakaran dan Penanggulangan Bencana Kota Bandung were high. Furthermore, work discipline had a significant and good effect on the employee performance of Dinas Kebakaran dan Penanggulangan Bencana Kota Bandung. The r square value indicates that work discipline has an enormous impact on an employee's performance.